Assessment of Quality of Underground Drinking Water: Very near (≤20 meters) and Far (>50 meters) from the River - Subedi, Munal; Magar, Mamata Gharti; Rajbhandari, Gita Shrestha (Nepal Journal of Biotechnology, 2017)
Water quality information is needed to assess the state of water contamination in a variety of community, including those that rely primarily on unimproved underground sources of drinking water. The study was carried out with an aim to assess the quality of ground water in particular sites of the Kathmandu valley. The ground water samples were collected from shallow well, tube well and deep tube wells located at specific places of the valley. The research was focused on physiochemical and bacteriological analysis of underground water from sites near to Bagmati river (≤20 meters) and from sites far from Bagmati river (>50 meters). The sampling sites were scattered from Sinamangal to Minbhavan. Total sample size was 100, with 50 in each stratum. Study processing was done during the period from February 2013 to May 2013. Six physiochemical parameters namely pH, Conductivity, Ammonia level, Chloride level, Nitrite level, Nitrate level and Biological parameters (Coliform and Fecal coliform) of each sample was tested. Based on the research work, it was recorded that the underground water close to river (≤20 meters) has comparatively high physiochemical and biological parameter (Fecal Coliform) than underground water that were farther from the river (>50 meters). Fecal Coliform was predominant 58% (29/50) in water nearer to river rather than in water farther from the river 20% i.e. (10/50). Similarly, the values of physiochemical and biological parameter increased comparatively with more distance i.e. ≤10 meters from river. The finding indicated that the underground water near to river is more polluted than far from the river. Nepal Journal of Biotechnology. Dec. 2017 Vol. 5, No. 1:21-26